On the convergence of workings and the purpose of working observations in salt mines - KORTAS, Grzegorz (Geology, Geophysics and Environment, 2012)
In this paper, the author has presented the definitions of convergence as a stream of displacement vector field. The author has presented equations of the convergence of workings (chambers, caverns), in the shape of geometric primitives, as well as identified and described the stages of convergence development in time. Basic principles of convergence are discussed, associating main convergences in a rectangular cavern with its dimensions and volumetric convergence. The current status of knowledge has been used for the formulation of the objectives of conducting convergence measurements in underground salt mines. The description of the convergence stages and the study of a rectangular chamber are educational in nature, while the identified objectives of observations can be applied for designing convergence observations and interpretation of results.